Information Literacy and the Internet: Transforming the Practice of Teaching and Corresponding Ethical Consequences - Gerald D. Bailey; David Pownell (Educational Considerations, 1999)
Technology pioneers have witnessed an interesting evolution of the computer over the last thirty years. In the 1970s, educators saw computers as a way of “crunching numbers.”